Eating behaviors and weight loss outcomes in a 12-month randomized trial of diet and/or exercise intervention in postmenopausal women - Caitlin Mason; Jean de Dieu Tapsoba; Catherine Duggan; Ching-Yun Wang; Catherine M. Alfano; Anne McTiernan (BMC, 2019)
Abstract Background Certain eating behaviors are common among women with obesity. Whether these behaviors influence outcomes in weight loss programs, and whether such programs affect eating behaviors, is unclear. Methods Our aim was to examine the effect of baseline eating behaviors on intervention adherence and weight among postmenopausal women with overweight or obesity, and to assess intervention effects on eating behaviors. Four hundred and 39 women (BMI ≥25 kg/m2) were randomized to 12 months of: i) dietary weight loss with a 10% weight loss goal ('diet'; n = 118); ii) moderate-to-vigorous intensity aerobic exercise for 225 mins/week ('exercise'; n = 117); iii) combined dietary weight loss and exercise ('diet + exercise'; n = 117); or iv) no-lifestyle change control (n = 87). At baseline and 12 months, restrained eating, uncontrolled eating, emotional eating and binge eating were measured by questionnaire; weight and body composition were assessed. The mean change in eating behavior scores and weight between baseline and 12 months in the diet, exercise, and diet + exercise arms were each compared to controls using the generalized estimating equation (GEE) modification of linear regression adjusted for age, baseline BMI, and race/ethnicity. Results Baseline restrained eating was positively associated with change in total calories and calories from fat during the dietary intervention but not with other measures of adherence. Higher baseline restrained eating was associated with greater 12-month reductions in weight, waist circumference, body fat and lean mass. Women randomized to dietary intervention had significant reductions in binge eating (− 23.7%, p = 0.005 vs. control), uncontrolled eating (− 24.3%, p < 0.001 vs. control), and emotional eating (− 31.7%, p < 0.001 vs. control) scores, and a significant increase in restrained eating (+ 60.6%, p < 0.001 vs. control); women randomized to diet + exercise reported less uncontrolled eating (− 26.0%, p < 0.001 vs. control) and emotional eating (− 22.0%, p = 0.004 vs. control), and increased restrained eating (+ 41.4%, p < 0.001 vs. control). Women randomized to exercise alone had no significant change in eating behavior scores compared to controls. Conclusions A dietary weight loss intervention helped women modify eating behaviors. Future research should investigate optimal behavioral weight loss interventions for women with both disordered eating and obesity. Trial registration NCT00470119 (https://clinicaltrials.gov). Retrospectively registered May 7, 2007.